Morris Graves : Selected Letters - Graves, Morris, 1910-2001 (Book collections on Project MUSE., 2013)
"Morris Graves is a major American painter with roots in the Pacific Northwest. Morris Graves: Selected Letters draws on a vast cache of the his unpublished correspondence, dating from his teenage years until his death in 2001. Few visual artists of any era have left such a rich and wide-ranging collections of letters, which makes this body of work an unusual and valuable document in American art. The Graves correspondence is remarkable for its scope, variety, and depth. Written to many correspondents over long periods of time, the letters include the artist's reflections on his art, the art world, philosophy (Zen Buddhism and Vedanta in particular), architecture (Graves designed his homes and gardens), and relationships with family, friends, and lovers. Graves himself preserved most of the letters, or copies of them, and put no restrictions on their use. Other letters come from a wide range of private and institutional sources. Among the correspondents are Graves's family; Marian Willard, his art dealer; Richard Svare, his companion in the 1950s; and Nancy Wilson Ross, novelist and Buddhist scholar. Other notable figures with whom Graves corresponded are poet Carolyn Kizer, art critic Theodore Wolff, curator Peter Selz, choreographer Merce Cunningham (for whom Graves created a set design), and painter Mark Tobey. Recurrent themes in the Graves letters are the tensions between sociability and solitude; the desire to be free of the material world versus the need for material comfort; the dismissal of commerce and the desperate need for money; the pleasures and pitfalls of love; and the difficulties of the creative life. The letters are organized topically under the broad categories of people (family, friends, intimates), places (homes and travels), and art (finances and philosophy). Independent curator Vicki Halper knew Graves toward the end of his life through her work as a modern art curator at the Seattle Art Museum. Lawrence Fong is the curator of American and regional art at the University of Oregon's Jordan Schnitzer Museum of Art. "A lively, valuable first-person resource by one of the region's most acclaimed artists. This collection of letters is refreshing for the fuller picture it provides of Graves's thoughts and actions. The notes identifying people and places in the correspondence are beautifully distilled, providing just enough to locate the letters without distracting from them."--Barbara Johns, author of Paul Horiuchi: East and West and Signs of Home: The Paintings and Wartime Diary of Kamekichi Tokita"This book is the essence of the rare written work of one of the most interesting artists of twentieth-century America. He is not only one of the essential figures in the American Northwest but also one of the leading artists between the Asian and western world."--Wulf Herzogenrath, Director, Kunsthalle Bremen"--